2014
DOI: 10.1111/iju.12587
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion‐weighted magnetic resonance imaging as an imaging biomarker of urothelial carcinoma

Abstract: Abbreviations & Acronyms ADC = apparent diffusion coefficient BC = bladder cancer CCRCC = clear cell renal cell carcinoma CRT = chemoradiotherapy DCE-MRI = dynamic contrast-enhanced magnetic resonance imaging DW-MRI = diffusion-weighted magnetic resonance imaging G = grade Ki-67 LI = Ki-67 labeling index MIBC = muscle-invasive bladder cancer MRI = magnetic resonance imaging NMIBC = non-muscle invasive bladder cancer NR = not reported P = pelvis Pts = patients ROI = regions of interest T2W-MRI = T2-weighted mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 60 publications
(118 reference statements)
1
15
0
1
Order By: Relevance
“…Yoshida et al . found that the additional use of DWI to T1WI and T2WI increases sensitivity with excellent interobserver agreement, and that DWI could be a useful adjunct to preoperative assessment of histological grade . Consistent with previous results, Yoshida et al .…”
Section: Significance and Limitations Of Mri Compared With Ctsupporting
confidence: 86%
See 1 more Smart Citation
“…Yoshida et al . found that the additional use of DWI to T1WI and T2WI increases sensitivity with excellent interobserver agreement, and that DWI could be a useful adjunct to preoperative assessment of histological grade . Consistent with previous results, Yoshida et al .…”
Section: Significance and Limitations Of Mri Compared With Ctsupporting
confidence: 86%
“…Recent studies reported that ADC inversely correlates with immunohistochemical and histological grading of upper UTUC and also that upper UTUC with lower ADC is more likely to have a metastatic potential . Therefore, ADC can be a biomarker that can predict the clinical course and prognosis of patients with upper UTUC . However, other studies reported that correlation between histological grade and ADC was controversial .…”
Section: Significance and Limitations Of Mri Compared With Ctmentioning
confidence: 99%
“…Diffusion‐weighted MR imaging (DWI) with apparent diffusion coefficient (ADC) has shown value for characterizing the aggressiveness of bladder cancer . Nevertheless, the conventional DWI‐derived ADC calculated with monoexponential model contains water molecular diffusion and microcirculation perfusion information.…”
mentioning
confidence: 99%
“…In bladder cancer management, DW-MRI has been reported to be useful in detection, characterization of histopathological features, prediction of therapeutic sensitivity, and therapeutic assessment [8,10,13,20,[22][23][24][25][26] . Recently, a high accuracy of DW-MRI has been reported during year- ly follow-up after TURB.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancers generally show a hyperintense signal because of their higher cellularity and tissue disorganization [8,9] . Since the first report showing the usefulness of DW-MRI in the detection of bladder cancer in 2007, DW-MRI has been increasingly applied in the management of bladder cancer [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%